Clinical Characteristic of Congenital Fetal Anomaly In Tertiary Referral Hospital in East Java, Indonesia - Amani, Fariska Zata; P, Wardhana M.; I, Cininta N.; A, Aryananda R.; E, Gumilar K.; I, Aldika M.; B, Wicaksono; Ernawati, Ernawati; A, Sulistyono; Aditiawarman, Aditiawarman; J, Hermanto T.; N, Abdullah; G, Dachlan E (UNUSA Press, 2021)
Background: Congenital fetal anomalies were defined as any structural defect present at birth. Congenital fetal anomalies are an important causes of neonatal morbidity and mortality in developed and developing countries that affect health care system. Reliable data on these congenital anomalies are still lacking, especially in Indonesia. Objective: This study aims to determine the characteristic profile of congenital fetal anomaly in single tertiary hospital in East Java, Indonesia. Methods: Retrospective cross-sectional by using medical record data of dr. Soetomo General Hospital on January – December 2017. Results: There were 58 cases (4,3%) with fetal congenital anomaly from 1360 deliveries in 2017. The majority of cases were referral cases (51 cases; 88%) and only seven cases were booked cases in obstetric outpatient dr. Soetomo General Hospital. Most of these congenital fetal anomaly cases ( 25 cases / 43,1%) were born from mother with ages 20 – 30 years old. Most cases (34 cases; 58,64%) were diagnosed first at third trimester (gestational age > 28 weeks). There were 36 cases (62%) had active termination of pregnancy. Thirty eight percent (22 cases) were born at 37-42 weeks and majority were born section caesaria. The three highest proportion of organ systems involved in fetal congenital anomalies were those of abdomen (22 cases; 37,9%); head (20 cases; 34,5%); thorax and muskuloskeletal (each 12 cases; 20,7%). Conclusion: The incidence of congenital fetal anomaly in dr. Soetomo Hospital at 2017 was 4,3%. Omphalocele and CTEV were two most common types of congenital fetal anomaly found. Most cases of congenital fetal anomalies have a poor prognosis, 67% cases born died. Further research about risk factors and comprehensive database are needed on cases of congenital anomaly to establish appropriate prevention and management.